Determinants of Child Marriage in Thailand: A Study among the Hmong Communities and Southernmost Provinces - Taesilapasathit, Chalalai (The Journal of Behavioral Science, 2024)
Background/ problem: Child marriage in Thailand has never received adequate academic recognition. Without knowledge of the fundamental determinants of child marriage in the country, it is difficult for Thailand to effectively deal with child marriage. Objective/ purpose: This study aimed to explore the determinants that facilitate the ongoing practice of child marriage in two areas of Thailand: the Hmong communities in the northern provinces and the Muslim communities in the southernmost provinces. Design and Methodology: A constructivist grounded theory research methodology was applied in this study, with the use of semi-structured interviews and focus group discussions as tools for data collection. A total of 113 participants voluntarily took part in this study. Findings: Three similar themes were found in both study areas: patriarchy and culture, a taboo of pre-marital sex and pregnancy outside of wedlock, and intergenerational oppression. The main differences among the Hmong communities and the Muslim communities in the south were the doctrines, which laid the cultural foundation for the two areas. Conclusion and Implications: The findings highlight the significant determinants that influence child marriage in the two study areas of Thailand. Any future programs aiming to eradicate child marriage in the country could apply the results from this study as foundations of their works. Originality/Value for the Sustainable Development Goals (SDGs): Preventing child marriage is listed under SDGs-5, which aims to combat gender inequality. With regards to the SDG-5, the UN urges member states to take action against child marriage and conduct academic research on this issue. However, the current studies on child marriage suggest that research on child marriage tend to be conducted in the regions where the rate of the practice is critically high, which Thailand is not included. This presents the gaps in child marriage research. This study addresses this gap by aiming to systematically study child marriage in rural Thailand. By focusing on the first-hand information from children, families, and communities, this study seeks to develop a model that explains determinants that support the existence of child marriage in rural Thailand.